Social Marketing Strategy of TBM Rumah Kreatif Sahabat Nusantara to Increase Reading Literacy Interest on Pulau Ende in 2022–2024 - Azhar, Iren Sadeva; Tri Hastuti Nur Rochimah (Jurnal Audiens, 2024)
The low reading literacy in Indonesia, especially in remote areas such as Ende Island, East Nusa Tenggara, is a serious problem that requires concrete solutions. One initiative to overcome this problem is through the Community Reading Park (TBM). This study aims to analyze the social marketing strategy implemented by TBM Rumah Kreatif Sahabat Nusantara in increasing reading literacy on Ende Island 2022-2024. With a social marketing theory approach and 6P elements (Product, Price, Place, Promotion, Policy, Partnership), this study uses a descriptive qualitative method through interviews, literature studies, and documentation. The results of the study show that TBM Rumah Kreatif Sahabat Nusantara has succeeded in developing a strategy that integrates culture and religion in its literacy program, as well as using collaborative promotion with an emotional approach and utilizing opinion leaders to influence people's reading interest. Collaboration with Al-Quran Learning Places (TPA) and schools strengthens program implementation. Supportive government policies also strengthen this strategy. However, TBM still faces obstacles in terms of limited funds and resources to support the continuation of the program.